2001
DOI: 10.1002/mrm.1300
|View full text |Cite
|
Sign up to set email alerts
|

Gd‐DTPA2–‐enhanced MRI of femoral knee cartilage: A dose‐response study in healthy volunteers

Abstract: The negatively charged contrast agent Gd-DTPA 2-distributes inversely to the cartilage fixed charged density. This enables structural cartilage examinations by contrast-enhanced MRI. In line with the development of a clinically applicable protocol for such examinations, this study describes the temporal pattern of Gd-DTPA 2-distribution in femoral knee cartilage at three different doses in healthy volunteers. Nineteen volunteers (ages 21-28 years) were examined with a 1.5T MRI system. Quantitative relaxation r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

16
127
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 117 publications
(144 citation statements)
references
References 30 publications
(41 reference statements)
16
127
1
Order By: Relevance
“…For T1, a good correspondence with the results of other research groups is seen (6,9,13,14). In the previous studies the calculated T1 relaxation values ranged from 300 to 580 msec for normal cartilage at 1.5T.…”
Section: Discussionsupporting
confidence: 71%
“…For T1, a good correspondence with the results of other research groups is seen (6,9,13,14). In the previous studies the calculated T1 relaxation values ranged from 300 to 580 msec for normal cartilage at 1.5T.…”
Section: Discussionsupporting
confidence: 71%
“…Gadolinium based biochemical MRI in the form of dGEMRIC (delayed gadolinium-enhanced MRI of cartilage) has been established as an important modality of articular cartilage imaging (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16). dGEMRIC is sensitive to the GAG content in the cartilage.…”
mentioning
confidence: 99%
“…This technique has been histologically validated (17,18) and previously used in numerous in vivo studies (5,8,9,(12)(13)(14)16) Recently, a fast T1 assessment technique using a dual flip angle (FA) gradient echo (GRE) technique in place of a standard inversion recovery (IR) for T1 mapping has been validated in phantom experiments and has also been used in vivo (10,19). This technique enables faster imaging time and the unique ability of three-dimensional (3D) T1-mapping.…”
mentioning
confidence: 99%
“…Therefore, T 1 -relaxation mapping subsequent to Gd-DTPA 2-administration reflects the underlying tissue charge and GAG content. This technique has been established in vitro (6)(7)(8) and in vivo (5,(9)(10)(11)(12)(13)(14).…”
mentioning
confidence: 99%
“…Key values of inversion time relaxation that provide information are T 10 (i.e., T 1 prior to contrast administration), T 1Gd (postcontrast T 1 ), and ⌬R 1 that defines the difference in relaxation rate (R 1 ϭ 1/T 1 ) between T 10 and T 1Gd measurements (1/T 1Gd Ϫ 1/T 10 ). According to some studies ⌬R 1 may be a more precise parameter to reflect the Gd-DTPA 2-concentration since precontrast T 1 variations can be factored in (12,13,15). Previous studies in the knee have reported that T 10 values differ minimally in early cartilage degeneration and that there is nearly a linear relationship between GAG content and T 1Gd (5,14,(16)(17)(18), making T 10 assessment in addition to T 1Gd unnecessary.…”
mentioning
confidence: 99%